2020
DOI: 10.7717/peerj.8957
|View full text |Cite
|
Sign up to set email alerts
|

Size-frequency distribution of coral assemblages in insular shallow reefs of the Mexican Caribbean using underwater photogrammetry

Abstract: The characterisation of changes in coral communities depends heavily on systematic monitoring programs and the collection of necessary metrics to assess reef health. Coral cover is the most used metric to determine reef health. The current organizational shift in coral requires the evaluation of complementary metrics, such as colony size and frequency distributions, which help to infer the responses of the coral populations to local stress or larger scale environmental changes. In this study, underwater digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 96 publications
0
15
0
Order By: Relevance
“…We found a significant but weak correlation between fish abundance and rugosity and vector dispersion metrics extracted from reconstructed 3D imagery of reef ( Young et al, 2017 ), although this may reflect the smaller scale (4 m 2 ) of reef habitat analysed ( Fukunaga et al, 2019 ). Hernández-Landa, Barrera-Falcon & Rioja-Nieto (2020) suggest 374 m 2 as the minimum sampling area to capture 90% of coral species richness for Caribbean systems with scale likely to play a major role in any analyses of this type. Previous studies have shown a lack of correlation between coral cover and structural complexity when coral cover is lower ( Graham et al, 2009 ) and this may have weakened relationships in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We found a significant but weak correlation between fish abundance and rugosity and vector dispersion metrics extracted from reconstructed 3D imagery of reef ( Young et al, 2017 ), although this may reflect the smaller scale (4 m 2 ) of reef habitat analysed ( Fukunaga et al, 2019 ). Hernández-Landa, Barrera-Falcon & Rioja-Nieto (2020) suggest 374 m 2 as the minimum sampling area to capture 90% of coral species richness for Caribbean systems with scale likely to play a major role in any analyses of this type. Previous studies have shown a lack of correlation between coral cover and structural complexity when coral cover is lower ( Graham et al, 2009 ) and this may have weakened relationships in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of our study could very well support coral reef conservation. Until now, coral reef studies applied different methods to map reefs as accurately as possible, aiming to improve the descriptors and determine the optimal level of sampling to monitor coral communities (e.g., Goreau, 1959;Weinberg, 1981;Leujak and Ormond, 2007;Casella et al, 2016;Fukunaga et al, 2019;Hernández-Landa et al, 2020). Scientists and managers often overlook the under or overestimation of coral cover, despite this being a crucial aspect when defining targets for resource conservation.…”
Section: Discussion Estimating Coral Covermentioning
confidence: 99%
“…Large-area imaging is an increasingly popular solution for the study of subtidal environments at scales of tens to hundreds of meters. In particular, orthographic imagery, e.g., orthophotomosaics, orthoprojections (for brevity, orthos), is increasingly being used for spatio-temporal analysis of coral communities [1][2][3][4][5]. Orthos enable the fine-scale mapping and accurate measurements of coral colony size and position that allow researchers to extract the information to better understand the demographic patterns and the spatial dynamics of benthic communities.…”
Section: The Semantic Segmentation Of Coral Reefsmentioning
confidence: 99%